The Disciplines of Vocal Pedagogy. Towards an Holistic Approach - Sell, Karen (Aldershot Ashgate, 2005)
If classical singers and vocal pedagogues are to be prepared adequately for performance, teaching and co-operation in inter-professional relations, then an holistic education entailing multi-disciplinary study is essential. In this important new book, Karen Sell examines the disciplines pertinent to vocal pedagogy, tracing the lineage of views from the ancient world to the present day. In the process important diverse roots are exposed, yielding differing and even conflicting tonal ideals which have a bearing on the consideration of different singing methods and the interpretation of songs and arias. Ethics and psychology are identified as central to the entire pedagogical process along with the scientific basis of singing: encompassing acoustics, anatomy and physiology, with special reference to the bearing of the latter two upon vocal health and hygiene. A detailed consideration of singing technique is the centrepiece of the book, and an understanding of good technique and scientific awareness is shown to be fundamental to good vocal pedagogical practice. This leads to a discussion on performance and aesthetics, contributing to the education of the fully equipped singer. No study to date has demonstrated the inter-relationships between all these individual disciplines and the ways in which they influence singing pedagogy. Sell?s holistic, multi-disciplinary approach will be of particular benefit to singers and voice teachers, and will also appeal to music educationalists and professionals in cognate disciplines.
Keywords: Vocal music; Singing; Method